PENGARUH HALAL AWARENESS, HARGA, DAN IKLAN TERHADAP KEPUTUSAN PEMBELIAN KOBER MIE SETAN DI SURABAYA - Ika Khusnia Anggraini; Az-Zahra, Narisa (Islamic Economics and finance in Focus, 2023)
Indonesia's Muslim population reaches 86.9% of the total population who in their daily life must carry out consumption. As an Islamic consumer, principles must be implemented in order to achieve blessings, such as consuming products that are guaranteed to be halal. The government has set a target for halal food in Indonesia to be number one in the world by 2023. The current condition is that there are still many products that do not have a halal label, such as Kober Mie Setan, but sellers provide advertisements and the prices are relatively cheap. Therefore, consumers are willing to queue to buy the food because of the unusual naming of the menu. The purpose of this study was to determine the effect of halal awareness, price, and advertising on purchasing desicion at Kober Mie Setan in Surabaya. This research is a quantitative study using the PLS-SEM analysis technique. The results show that halal awareness has no significant effect on purchasing decisions for Kober Mie Setan in Surabaya. Prices and advertising partially have a significant effect on purchasing decisions for Kober Mie Setan in Surabaya